Pseudovibrio flavus sp. nov. isolated from the sea sponge Verongula gigantea. Issue 8 (2nd August 2022) - Goldberg, Stacey R.; Haltli, Brad A.; Correa, Hebelin; Kerr, Russell G.
Abstract : A Gram-negative, motile, rod-shaped marine bacterium, designated RKSG542 T, was isolated from the sea sponge Verongula gigantea collected at a depth of 20 m off the west coast of San Salvador, The Bahamas. Phylogenetic analyses based on 16S rRNA gene and genome sequences place RKSG542 T in a monophyletic clade with members of the genus Pseudovibrio . Strain RKSG542 T shared <96.7 % 16S rRNA gene sequence similarity, <72.2 % average nucleotide identity, <66.7 % average amino acid identity, and <24.8 % digital DNA–DNA hybridization with type strains of the family Stappiaceae . Growth occurred at 22–37 °C (22–30 °C optimum), at pH 7–9 (pH 7 optimum), and with 0.5–5 % (w/v) NaCl (2 % optimum). The predominant fatty acids (>10 %) were summed feature 8 (C18 : 1 ω 6 c and/or C18 : 1 ω 7 c ), C18 : 0 and C16 : 0, and the respiratory lipoquinone was Q-10. The polar lipid composition comprised phosphatidylethanolamine, phosphatidylglycerol, diphosphatidylglycerol, three unknown aminolipids, six unknown phospholipids and four unknown lipids. The DNA G+C content of the genome sequence was 52.5 mol%. Based on the results of biochemical, phylogenetic and genomic analyses, RKSG542 T (=TSD-76 T =LMG 29867 T ) is presented here as the type strain of a novel species within the genus Pseudovibrio (family Stappiaceae, order Hyphomicrobiales, class Alphaproteobacteria ), for which the name Pseudovibrio flavus sp. nov. is proposed.